Sacred violence : torture, terror, and sovereignty - Kahn, Paul W., 1952- (Law, meaning, and violence., 2008)
"In Sacred Violence, Paul W. Kahn investigates the reasons for the resort to violence characteristic of premodern states. He contends that law will never offer an adequate account of political violence. Instead, we must turn to political theology, which reveals that torture and terror are, essentially, forms of sacrifice. Kahn forces us to acknowledge what we don't want to see: that we remain deeply committed to a violent politics beyond law."--Jacket